Analiza različnih pristopov pri izvedbi digitalizacije gozdnih prometnic - Rebolj, Luka (Gozdarski vestnik, 2015)
Quality data represent the basis for planning work processes. As a rule, quality of data improves with the development of data acquisition technologies, since they enable acquisition of accurate information on surface, also forested one, in whose framework fairly accurate information on forest traffic roads can be acquired. Accurate acquisition of data on forest traffic roads is important both in forest management planning and in carrying out of the planned activities. In this article we analyze time consumption and accuracy of acquisition of data on forest traffic roads from diverse sorts of remotely acquired data and diverse data acquisition methods, our goal being to determine the most favorable method. The article presents the comparison of data acquisition using GPS recordings in the field and acquisition using LiDAR data. The analysis took place in the Begunjščica pilot area, situated in the central part of Karavanks Mountain Range for which quality LiDAR data are available, showing the fact that accuracy and time consumption are more favorable when using LiDAR data.
Keywords: gozdne prometnice; gozdne ceste; gozdne vlake; poraba časa; digitalizacija; digitization; LiDAR; daljinsko zaznavanje